Modeling of thermal stresses on steel beam - Dalipi, Bashkim; Syla, Naim; Aliaj, Fisnik; Zeqiraj, Arbër (International Journal of Computational and Experimental Science and Engineering, 2025)
When a metal separates two environments with different temperatures, then because of the temperature gradient in the metal, thermal stresses will appear. To address this phenomenon, we will take the example of a steel beam, which is part of a metal construction. The geometry of the beam is regular and one end of it is subjected to a continuous emission of heat (for example, it is close to the oven) while the other end is in contact with the surrounding external environment. For simplicity, we will assume that the heat emission is constant, so the temperature of the edge of the beam is also constant. Likewise, for the temperature of the other end, we will assume that it is constant. Let the temperature of the first end be , while that of the second end is , then the difference causes the flow of heat, respectively the occurrence of thermal stresses. Mathematically, heat flow is described by a differential equation in the temperature field, while the functional dependence of the deformation is described by a differential equation in the field of structures - Hooke’s law. So, we have two differential equations from two fields: thermal and structural. We have solved them with the finite element method in temperature-structure coupled field, while the simulation in ANSYS. The algorithm of the FE method and the simulation in ANSYS prove that the treatment can be done for other integration conditions (geometry, material and different temperatures).